An in Silico Analysis of Physicochemical Characterization and Protein-Protein Interaction Network Analysis of Human Anti-apoptotic Proteins (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Apoptosis is a physiological mechanism, playing an essential role in regulating development,homeostasis, and immune defense by removing abnormal cells in organisms. A balance between pro-apoptotic andanti-apoptotic mechanisms determines cell death signal where the pro-apoptotic proteins promote apoptosis andanti-apoptotic proteins inhibit apoptosis. In general, the inhibitors of apoptosis proteins (IAPs) inhibit the caspaseactivation pathways and play an important roles in regulating apoptosis in many species. Methodology: A total of50 different human anti-apoptotic proteins retrieved from UniProt Database were analyzed and characterized usingin silico tools. A parsimonious phylogenetic tree for these proteins was constructed using the Poisson correctionmodel. Genomic and proteomic data are often combined with protein-protein interaction networks (PPIN) whosestructure is routinely analyzed by tools to characterize hubs for treating cancer. Results and Discussion: Primarystructure analysis shows that most of the anti-apoptotic proteins are hydrophilic in nature due to the high contentof glutamate and serine residues. The presence of disulfide bonding 27 proteins infers that these proteins mayform disulfide bonds, which are regarded as a positive factor for stability. The aliphatic index computed byExpasy’s ProtParm infers that these proteins may be stable for a wide range of temperature. Secondary structureanalysis shows that most of the human anti-apoptotic proteins have predominant coiled structures due to therich content of more flexible glycine and proline amino acids. Top 10 hub proteins were identified using PPINanalysis. Conclusion: Thus, the characterization of human anti-apoptotic proteins provides additional targets andnew therapeutic approaches for treating cancer.